Working therapeutically with women in secure mental health settings - Jeffcote, Nikki, 1959-; Watson, Tessa, 1967- (London ; New York : Jessica Kingsley Publishers, 2004)
A pressing need for the integration of current practice, research and service development is addressed in this comprehensive book, which explores the experience of work with women in secure mental health settings. The first section offers different perspectives on the needs and situations of this minority population. It includes consideration of the differing needs of women and men, and key environmental and therapeutic issues highlighted by recent research and service provision. Further chapters cover clinical illustrations of work with women in different settings, including descriptions of i.
I: Theory-building -- Thinking about the needs of women in secure settings. -- Dangerous journeys: women's pathways into and through secure mental health -- Services. -- Women and offending. -- Troubled inside: vulnerability in prison. -- Women and risk. -- More alike than different: gender and forensic mental health -- II. Practice -- Working together: integrated multi-disciplinary practice with women. -- Thinking under fire: the challenge for forensic mental health nurses working -- With women in secure care. -- Hiding and being lost: the experience of female patients and staff on a -- Mixed sex ward. -- 'a net of threads finer than cobweb': the life of a women's group. -- A psychodynamically-orientated group for women with learning disabilities. -- III: Service development -- The development of medium secure services for women. -- Closing the gap between evidence and practice: the role of training in -- Transforming women's services. -- Men, women, and good practice.
Includes bibliographical references (pages 202-211) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Women prisoners -- Mental health services; Women prisoners -- Mental health; Mentally ill offenders -- Mental health services; Female offenders -- Mental health services; Forensic psychiatric nursing; Mental health services; Forensic psychiatry; Psychiatric hospitals; Mental Health Services; Prisoners -- psychology; Forensic Psychiatry; Hospitals, Psychiatric; Institutionalization; Mentally Ill Persons -- psychology; Women -- psychology; United Kingdom; Psychiatric Department, Hospital; Prisonnières -- Services de santé mentale; Prisonnières -- Santé mentale; Criminels vivant avec un trouble de santé mentale -- Services de santé mentale; Criminelles -- Services de santé mentale; Soins infirmiers médico-légaux en psychiatrie; Services de santé mentale; Psychiatrie médico-légale.; Hôpitaux psychiatriques; Hôpitaux -- Services de psychiatrie; psychiatric hospitals; Psychotherapy; Pathology; SOCIAL SCIENCE -- Penology; Psychiatric hospitals; Mental health services; Forensic psychiatry; Forensic psychiatric nursing; Mentally ill offenders -- Mental health services; Women prisoners -- Mental health; Women prisoners -- Mental health services